2019
DOI: 10.3390/fluids4030168
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Density-Driven Flow in Fractured Porous Media: The Fractured Elder Problem

Abstract: The Elder problem is one of the well-known examples of an unstable density-driven flow (DDF) and solute transport in porous media. The goal of this research is to investigate the influence of fracture networks on this benchmark problem due to the great importance of the fractured heterogeneity effect on unstable DDF. For this aim, the fractured Elder problem is solved using COMSOL Multiphysics, which is a finite element method simulator. Uniform and orthogonal fracture networks are embedded to analyze free con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The kinetic dissolution reactions are included as source terms in the transport equations. To include fractures via the discrete fracture approach (1D), we used the interface "Fracture flow" as in (Koohbor et al, 2019;Mozafari et al, 2018;Shafabakhsh et al, 2019). The system of flow and transport equations are solved simultaneously using the fully coupled approach in COMSOL.…”
Section: Conceptual and Numerical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic dissolution reactions are included as source terms in the transport equations. To include fractures via the discrete fracture approach (1D), we used the interface "Fracture flow" as in (Koohbor et al, 2019;Mozafari et al, 2018;Shafabakhsh et al, 2019). The system of flow and transport equations are solved simultaneously using the fully coupled approach in COMSOL.…”
Section: Conceptual and Numerical Modelsmentioning
confidence: 99%
“…The effects of fractures on non-reactive DDC processes have been extensively investigated in the literature but not in the context of CO2 sequestration (Hirthe and Graf, 2015;Jafari Raad and Hassanzadeh, 2018;Shafabakhsh et al, 2019;Simmons et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The leaking of concentrated brines would prevent the salt flats to reach extremely high concentrations (Sanford and Wood, 1991). Furthermore, fault planes are frequently associated with preferential flow paths due to their higher permeability combined with the development of convective cells (Barcelona et al, 2019;Hirthe and Graf, 2015;Koltzer et al, 2017;Li et al, 2016;Magri et al, 2016Magri et al, , 2015Magri et al, , 2010Shafabakhsh et al, 2019;Simms and Garven, 2004;Zechner et al, 2019). However, although previous work has highlighted the necessity of addressing thermohaline circulation in salt flats (e.g., Godfrey and Álvarez-Amado, 2020;Hardie, 1991Hardie, , 1990Magaritz et al, 1990;Munk et al, 2016;Risacher et al, 2003;Rosen, 1994), only synthetic models focused on the saline interface of the shallowest aquifers have been performed to date (Duffy and Al-Hassan, 1988;Fan et al, 1997;Hamann et al, 2015;Holzbecher, 2005;Marazuela et al, 2018;Nield et al, 2008;Simmons et al, 1999;Tejeda et al, 2003;Vásquez et al, 2013).…”
Section: Figurementioning
confidence: 99%
“…Salibindla et al (2018) conducted an experimental investigation of the dissolution convection in a porous medium with multiscale heterogeneity and some important implications for the future estimation of subsurface carbon sequestration were presented. Shafabakhsh et al (2019) considered the influence of a fractured heterogeneity effect on unstable density-driven flow. It was shown that the onset of instability and free convection occur with a lower critical Rayleigh number, indicating the fractured networks have a destabilizing effect.…”
Section: Introductionmentioning
confidence: 99%
“…Shafabakhsh et al. (2019) considered the influence of a fractured heterogeneity effect on unstable density-driven flow. It was shown that the onset of instability and free convection occur with a lower critical Rayleigh number, indicating the fractured networks have a destabilizing effect.…”
Section: Introductionmentioning
confidence: 99%